The effect of collagen hydrolysates from silver carp (Hypophthalmichthys molitrix) skin on UV-induced photoaging in mice: molecular weight affects skin repair. Issue 4 (7th March 2017) - Song, Hongdong; Meng, Mengfei; Cheng, Xiaofeng; Li, Bo; Wang, Chengtao
Abstract : LMCH exerted stronger beneficial effects on photoaging skin than HMCH and gelatin. Abstract : The use of collagen hydrolysates (CHs) as a nutraceutical agent in skin aging has gained increasing attention. Here, the effects of various doses and molecular weights of CH from silver carp skin on photoaging in mice were investigated. The ingestion of CH at 50, 100 and 200 mg per kg body weight led to a dose-dependent increase in the hydroxyproline, hyaluronic acid and moisture contents of the skin, but it had no significant effect on the mice body weight, or on the spleen or thymus index. Furthermore, ingesting CH with lower (LMCH, 200–1000 Da, 65%) and higher molecular weight (HMCH, >1000 Da, 72%) significantly increased the skin components and improved the antioxidative enzyme activities in both serum and skin ( p < 0.05); LMCH performed better than HMCH. By contrast, gelatin (>120 kDa) ingestion did not bring a significant change compared to model mice. These results indicated that LMCH exerted a stronger beneficial effect on the skin than did either HMCH and gelatin, which supported the feasibility of using LMCH as a dietary supplement from silver carp skin to combat photoaging.